Children's healthy and unhealthy beverage availability, purchase and consumption: A wearable camera study. (1st February 2019) - Smith, Moira; Stanley, James; Signal, Louise; Barr, Michelle; Chambers, Tim; Balina, Alexis; Ni Mhurchu, Cliona; Wilson, Nick
Abstract: Children's sugar-sweetened beverages (SSBs) consumption presents significant risks for obesity, type 2 diabetes and dental health. But there is a lack of objective data on beverages in children's overall environments. This study aimed to determine the nature and extent of children's beverage availability, purchase and consumption, throughout their day, using wearable cameras for data collection. Data were sourced from 'Kids'Cam NZ′, a study in which randomly-selected New Zealand children (n = 168; 11-14y, mean 12.6y) wore cameras for four days (Thursday-Sunday), automatically taking a photo every 7s. Using content analysis, Thursday and Saturday images (n = 700, 201) were systematically analysed. On average, 18.9 (95% CI 16.8, 21.4) drinks/day were available to the children (n = 158), of which 7.5 (95% CI 5.8, 9.7; 39.7%) were non-core drinks, including 6.4 (95% CI 5.0, 8.3; 33.9%) SSBs. At school and home, core drinks (water and unflavoured milk) were the most available. In all other locations in which children spent time (e.g., recreation venues and food retail outlets) non-core drinks dominated, at rates 1.5–5 times that of core drinks availability. Almost all drinks (n = 17; 10.8%) the children purchased were non-core. On average, children (n = 111; 70.3%) consumed a drink 2.6 (95% CI 2.1, 3.1) times/day, including one (95% CI 0.7, 1.3) SSB. At school and home core drinks predominated. SSBs were available to most children in all locations in which they spent time, and dominated their drinks purchases and consumption. SSBs appear to be a typical feature of children's everyday environments, almost certainly making it difficult for children's beverage intakes to align with guidelines. The findings support calls for governments to urgently enact the SSB-related actions in the WHO Commission's Ending Childhood Obesity implementation plan and, in turn, improve child health.